In Search of a Cultural Background: The Recommended Reading Lists of Alfred Lawrence Kocher and the Beauty of Utility in 1920s America - Canato, Mario (Enquiry The ARCC Journal for Architectural Research, 2020)
The modernist architect and critic, Alfred Lawrence Kocher, proposed and commented on many bibliographical references in the Architectural Record in the years 1924-25. Recent studies on American architecture of the 1920s and 1930s have recognized the peculiar character of modernism in the United States and have gone in search of its cultural and social roots. However, Kocher’s extensive lists have so far been completely overlooked. They were based for the most part on the correspondence he exchanged with a number of American and British architects and George Bernard Shaw: he had sent to them a circular letter, asking for recommendations on texts on background literature that a young architect should know. The unpublished correspondence that Kocher had with Louis Sullivan and the 19 texts on “Aesthetics and Theory of Architecture” are analyzed in particular by the author. Although from 1927 onwards Kocher became a passionate supporter of European rationalist architecture, his bibliographies cannot be considered a conscious foundational literature on modernism and modernity. They rather give an idea of the ‘cultural trunk’ on which the discussion on modern European architecture was going to be grafted; they help to illuminate the scene on which American architects moved in the mid-1920s. In some of the texts, the pragmatic notion of utility shines through, as ? sometimes connectedly ? does the concept of a creative act as a free, ‘natural’ act, which derived from American transcendentalism. Independent from Kocher’s will, a line of thought is even identifiable, through which one can explain the apparently contradictory combination of ‘maximum of utility’ and ‘maximum of free creativity’, openly advocated by the skyscraper architect Raymond Hood at the end of the 1920s. Such way of thinking was based on the recognition of the beauty of utility.